2013
DOI: 10.1109/jphot.2013.2272781
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Lasing Operation From Chirped InAs/InP Quantum-Dash Laser

Abstract: We study the enhanced inhomogeneity across the InAs quantum-dash (Qdash) layers by incorporating a chirped AlGaInAs barrier thickness in the InAs/InP laser structure. The lasing operation is investigated via Fabry-Pe ´rot ridge-waveguide laser characterization, which shows a peculiar behavior under quasi-continuous-wave (QCW) operation. Continuous energy transfer between different dash ensembles initiated quenching of lasing action among certain dash groups, causing a reduced intensity gap in the lasing spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The SW, MW, and LW group of longitudinal modes are the characteristics (being resonant with) of S 20 , S 15 , and S 10 Qdash stacks, respectively. We explained this anomalous observation in greater detail by considering a qualitative carrier-feeding model, very recently [24]. In the following, we briefly address the cause of this spectral split from the angle of highly inhomogeneous Qdash system, although, we cannot exclude the possibility of different non-linear phenomena occurring in the active region that affects the carrier-photon interaction, particularly, spectral and spatial hole burning effects, and the retarded carrier diffusion (due to potential fluctuations in the Qdash active region) and photon re-absorption (including the outer part of the ridge-waveguide) induced change in lateral index step and lateral gain distribution allowing higher order lateral mode to emerge [25]- [27].…”
Section: A Ridge-waveguide Lasersmentioning
confidence: 98%
“…The SW, MW, and LW group of longitudinal modes are the characteristics (being resonant with) of S 20 , S 15 , and S 10 Qdash stacks, respectively. We explained this anomalous observation in greater detail by considering a qualitative carrier-feeding model, very recently [24]. In the following, we briefly address the cause of this spectral split from the angle of highly inhomogeneous Qdash system, although, we cannot exclude the possibility of different non-linear phenomena occurring in the active region that affects the carrier-photon interaction, particularly, spectral and spatial hole burning effects, and the retarded carrier diffusion (due to potential fluctuations in the Qdash active region) and photon re-absorption (including the outer part of the ridge-waveguide) induced change in lateral index step and lateral gain distribution allowing higher order lateral mode to emerge [25]- [27].…”
Section: A Ridge-waveguide Lasersmentioning
confidence: 98%
“…The nominal InAs layer thickness in each group was varied from 0.91 nm to 1.31 nm [5]. Very recently, our group demonstrated a broad PL linewidth from a chirped InGaAlAs barrier 4-stack DaWELL laser structure [223] based on the systematic study on the effect of barrier thickness on the active region inhomogeneity [224]. By employing variable barrier thickness of 10 nm (p-side), 10 nm, 15 nm, and 20 nm (n-side), we demonstrated an ultra-broad 77 K PL linewidth of ~151 nm and found a significant increase in the linewidth when compared to a 4 stack fixed 10 nm barrier similar Qdash laser sample (77 K PL linewidth ~100 nm).…”
Section: Chirped Qdash Active Region Designmentioning
confidence: 99%
“…Soon after, Reithmaier et al [30] reported a large gain-bandwidth of 270 nm with peak gain of 40 cm À1 using a similar chirped design of 4 varying InAs layers at a fixed barrier layer. Based on the analytical results of the thickness of the barrier layer on the inhomogeneity of the structure [31], our group demonstrated [32] an ultrabroad PL linewidth of w151 nm by utilizing a chirped 4-stack InGaAlAs DaWELL structure with varying barrier layers (20, 15, 10, 10 nm) that was drastically broader than a similar structure of a fixed barrier layer thickness (10 nm) among the different layers where the PL linewidth was w100 nm. Under continuous wave (CW) current density of 8.3 kA/cm 2 , the gain-bandwidth was measured [33] as w140 nm with a peak modal gain of w41 cm À1 as shown in Fig.…”
Section: Inas/ingaasp Materials Systemmentioning
confidence: 99%
“…The laser displayed a per-layer threshold current density of 900 A/cm 2 and a slope efficiency 0.36 W/A. Furthermore, we investigated the device physics of the chirped structure and postulated that simultaneous emission for dispersive Qdashes [33] and the nonuniform distribution of carriers in the Qdash active region [32] play a significant role in the observed broad emission. Very recently, we further investigated the detailed thermal characteristics of the InAs/InP Qdash broadband laser with different ridge widths in terms of junction and characteristics temperatures [54].…”
Section: Inas/inp Qdash Ultra-broadband Lasersmentioning
confidence: 99%